Biodegradation of octogen and hexogen by Pelomonas aquatica strain WS2-R2A-65 under aerobic condition. Issue 7 (21st March 2022) - Nagar, Shilpi; Shaw, Ajay Kumar; Anand, Shalini; Celin, S. Mary; Rai, Pramod Kumar
Abstract: Biodegradation ability of a native bacterial species Pelomonas aquatica strain WS2-R2A-65, isolated from nitramine explosive-contaminated effluent, for octogen (HMX) and hexogen (RDX) under aerobic condition has been explored in this study. Scanning electron microscopy indicated that the isolate WS2-R2A-65 retained its morphology both in the presence and absence of HMX or RDX. During an incubation period of 20 days, the isolate cometabolically degraded 78 and 86% of HMX and RDX with initial concentrations 6 and 60 mg L −1, respectively. The degradation mechanism followed the first-order kinetics for both the nitramines with a 50% degradation time of 9.9 and 7.7 days for HMX and RDX, respectively. Positive electrospray ionisation mass spectroscopy indicates that biodegradation of nitamines follows multiple degradation pathways with one involving ring cleavage via single-electron transfer to nitramines leading to the elimination of single nitrite ion as evident from the formation of methylenedinitramine (MEDINA) and its methyl derivatives. The other pathways involve the reduction of both the nitramines to their nitroso, hydroxylamino and amino derivatives. These metabolites get further ring cleaved to give secondary metabolites viz. N -hydroxymethylmethylenedintramine, N -nitrosoamino and hydrazinyl derivatives leading to simpler less hazardous end products. Thus, the isolate WS2-R2A-65 proves to be an efficient microbial species for bioremediation of nitramines-contaminated effluent. GRAPHICAL ABSTRACT: UF0001